Hubungan Dukungan Suami dan Pengetahuan Ibu Hamil dengan Kunjungan Antenatal (K1 Standar) di Unit Pelaksana Teknis Dinas Puskesmas Sidemen - Ni Ketut Sudiari; I gusti Agung Ayu Novya Dewi; Ni Komang Yuni Rahyani (Malahayati Nursing Journal, 2025)
ABSTRACT The first trimester antenatal visit is the first contact with health personnel or having received first pregnancy services in health services according to 10T standards. Factors that influence mothers to make K1 visits include parity, age, knowledge, attitudes, economics, socio-culture, geography, information and support. The results of a preliminary study conducted on 10 pregnant women showed that seven pregnant women (70%) did not know about the importance of antenatal visits in the first trimester and five pregnant women (50%) did not receive full support from their husbands to carry out antenatal visits. The aim of this research was to analyze the relationship between husband's support and knowledge of pregnant women with antenatal visits (K1 standard) at the Sidemen Health Center UPTD. This research is correlative analytical research using a cross-sectional study approach. The implementation of this research will start from February-April 2024 using a non-probability sampling technique, namely purposive sampling. The sample consisted of 51 respondents and data collection was carried out by distributing questionnaires. Data analysis used univariate in the form of a frequency distribution and bivariate using the Contingency Coefficient test with a significance level of p0.05. The results of the research show that there is a significant relationship between husband's support and antenatal visits (K1 standard) with a value of p = 0.001 and there is a significant relationship between knowledge of pregnant women and antenatal visits (K1 standard) where the value of p = 0.000.  Keywords: Husband's Support, Knowledge of Pregnant Women, Antenatal Visit (K1 Standard)  ABSTRAK Kunjungan antenatal trimester pertama merupakan kontak pertama dengan tenaga kesehatan atau telah mendapatkan pelayanan kehamilan pertama di pelayanan kesehatan sesuai standar 10T. Faktor yang mempengaruhi ibu melakukan kunjungan K1 diantaranya paritas, usia, pengetahuan, sikap, ekonomi, sosial budaya, geografis, informasi dan dukungan. Tujuan dilakukan penelitian ini adalah untuk menganalisa hubungan dukungan suami dan pengetahuan ibu hamil dengan kunjungan antenatal (K1 standar) di UPTD Puskesmas Sidemen. Penelitian ini merupakan penelitian analitik korelatif dengan menggunakan pendekatan cross sectional study. Pelaksanaan penelitian ini mulai bulan Pebruari-April 2024 di UPTD Puskesmas Sidemen dengan teknik non probability samplingyaitu purposive sampling. Sampel berjumlah 51 responden dengan instrument menggunakan kuesioner. Analisis data univariat dalam bentuk distribusi frekuensi dan bivariat menggunakan uji koefisien kontingensi dengan tingkat kemaknaan p0,05. Hasil penelitian menunjukkan dukungan suami terbanyak yaitu kategori baik, pengetahuan ibu hamil terbanyak yaitu kategori baik, kunjungan antenatal terbanyak yaitu sudah sesuai standar, terdapat hubungan yang signifikan antara dukungan suami dengan kunjungan antenatal (K1 Standar) dengan nilai p = 0,001 serta terdapat hubungan yang signifikan antara pengetahuan ibu hamil dengan kunjungan antenatal (K1 standar) dimana nilai p = 0,000.  Kata Kunci: Dukungan Suami, Pengetahuan Ibu Hamil, Kunjungan Antenatal (K1 Standar)